Prospective LCA to support the agri-food sector’s transition towards sustainability—89th LCA discussion forum conference report - Mélanie Douziech; Christian Bauer; Maria Bystricky; Vasco Diogo; Pierre Jouannais; Jens Lansche; Eléonore Loiseau; Joan Muñoz-Liesa; Anne van den Oever; Thomas Nemecek (The International Journal of Life Cycle Assessment, 2025)
Purpose The 89th Life Cycle Assessment (LCA) Discussion Forum (DF) on the use of prospective LCA (pLCA) to support sustainability transitions of the agri-food sector was held on the 4th of February 2025 in Zurich. Methods This paper summarizes the main discussion points and challenges identified during the 89th LCA DF related to pLCA in the agri-food sector. Results The presentations highlighted recent progress in inventory and impact modelling and featured case studies related to the technology- and system-wide application of pLCA to the agri-food sector. The Q&A sessions and panel discussion highlighted challenges related to pLCA in the agri-food sector and in general. These challenges relate to missing data, the complexity of pLCA and its associated uncertainties, as well as ensuring the usefulness of the conducted evaluations. Possible solutions relate to streamlining the communication of results, adapting them to the needs of different stakeholder groups, or exploring scenarios to showcase a range of possible futures. Additionally, more frequent collaboration with other research fields could help reduce uncertainty and improve data availability. Conclusions While the challenges faced in the pLCA of agri-food systems are similar to those in other sectors, the lack of data on future developments and uncertainties is more pronounced. This is largely due to the dynamic character of these systems and their sensitivity to environmental conditions .

Effects of water protection measures in agriculture on the environmental impacts of the Swiss food sector - Maria Bystricky; Cédric Furrer; Christian Ritzel; Thomas Nemecek; Gérard Gaillard (Journal of Cleaner Production, 2024)

Correction: Swiss Agricultural Life Cycle Assessment: A method to assess the emissions and environmental impacts of agricultural systems and products - Thomas Nemecek; Andreas Roesch; Maria Bystricky; Philippe Jeanneret; Jens Lansche; Martin Stüssi; Gérard Gaillard (The International Journal of Life Cycle Assessment, 2024)

Swiss Agricultural Life Cycle Assessment: A method to assess the emissions and environmental impacts of agricultural systems and products - Thomas Nemecek; Andreas Roesch; Maria Bystricky; Philippe Jeanneret; Jens Lansche; Martin Stüssi; Gérard Gaillard (The International Journal of Life Cycle Assessment, 2024)
Purpose Agricultural production, which dominates the environmental impacts of the food sector, has specific characteristics that need to be considered in life cycle assessment (LCA) studies. Agricultural systems are open, difficult to manage and control, strongly depend on natural resources and their impacts are highly variable and influenced by soil, climate and farm management. A specific framework, efficient methods and tools are thus needed to adequately assess the environmental impacts of agricultural systems. Methods We present the Swiss Agricultural Life Cycle Assessment (SALCA) concept and method, developed for a detailed and specific analysis of agricultural systems. It comprises rules for the definition of system boundaries, functional unit and allocation, emission models, a life cycle inventory (LCI) database, calculation tools, impact assessment methods and concepts for analysis, interpretation and communication. This paper focuses on emission models for gaseous N, nitrate leaching, P emissions to water, soil erosion, pesticides, heavy metals, emissions from animal production and impact assessment methods for soil quality and biodiversity. The models are calculated at the crop, field, animal group and farm levels and are integrated in a consistent and harmonised framework, which is ensured by exchanging intermediate results between models. Results and discussion The SALCA concept has been applied in numerous LCA studies for crops and crop products, cropping systems, animal husbandry systems and animal products, food and feed products, farms and product groups, the agrifood sector and food systems. The SALCA methodology has also been a backbone of the LCI databases ecoinvent, AGRIBALYSE and the World Food LCA database. The strengths of SALCA lie in its comprehensiveness, specificity to agriculture, harmonisation, broad applicability, consistency, comparability, flexibility and modularity. The extensive data demand and the high complexity, however, limit the application of SALCA to experts. The geographical scope is limited to Central and Western Europe, with a special focus on Switzerland. However, due to the modular and flexible design, an adaptation to other contexts is feasible with reasonable effort. Conclusions SALCA enables answering a wide range of research questions related to environmental assessment and is applicable to various goals and scopes. A further development would be the inclusion of the social and economic dimensions to perform a full sustainability analysis in the SALCAsustain framework.